PENGARUH PEMBANGUNAN JALAN TERHADAP PERUBAHAN PENGGUNAAN LAHAN PADA KAWASAN HUTAN KONSERVASI PULAU KECIL DI TAMAN BURU PULAU REMPANG, BATAM - , Budi Susetyo; , Ir. Kawik Sugiana, M. Eng, Ph. D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rempang Island is small island that is part of the bonded zone of Batam Industrial Area and as well as a hunting park forest conservation. Construction of roads and bridges connecting the island to the center of industrial and government activities on the island of Batam and the surrounding hinterland areas, increase accessibility to the forest and causing changes in forest land into various forms of agricultural land, residential, public facilities, government, commerce and services. The purpose of this study is to determine the effect of road construction on land use change, the characteristics and chronological changes of land use and the impact on the environment and society of Rempang Island which has a uniqueness as small island forest ecosystem. The research method used is mixed methods with quantitative and qualitative approaches. Quantitative analysis was done by linear regression analysis between the independent variable road density, and the dependent variables land-use changes (agricultural land, forest land, open land and built land) during the 1989 to 2012. Qualitative analysis was done by observation and in-depth interviews of the 35 informants were selected purposively. The results showed that the increase in road density significantly affected changes in lowland forest, agricultural land and built land, but did not significantly affect changes in open land. Changes in land use in the period before the construction of roads and bridges completed in 1998, was more influenced by the following factors: (1) poverty, lack of employment opportunities in the place of origin as well as the desire to improve the well-being, encouraging people doing encroachment and forest clearance for agriculture and settlement, (2) lack of law enforcement against land-use change. In the period after 1998, land-use changes has been growing along with the development and construction of Rempang Island as an area of land reserves for industrial, commercial, residential and government, as well as along with lack of law enforcement, related to its status as forest conservation area. Construction of road networks in the form of a direct impact, damage forest conservation, and indirect impacts such as logging and illegal sand mining, extraction of natural resources, changes in local culture, communities and conflict use or land ownership. The proposed recommendation is the need to re-evaluate the status of Rempang Island Hunting Park, rearranges the remaining forests, accompanied by stricter law enforcement and control of development on the island.